ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 65/PUU-IX/2011 TENTANG PRAPERADILAN DI INDONESIA - Achmad Zuhdi (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTPre-Trial is formed to promote the rights of suspects, but found many injustice in this pre-trial mechanism. in Article 83 Verse (2) Criminal Procedure Code grants the right only to investigators when a decision relating to the validity or not of the investigation / validity of the prosecution if it is decided by the